2009
DOI: 10.1007/s00018-009-0154-8
|View full text |Cite
|
Sign up to set email alerts
|

Activation and repression of prion protein expression by key regions of intron 1

Abstract: Expression of the prion protein is necessary for infection with prion diseases. Altered expression levels may play an important role in susceptibility to infection. Therefore, understanding the mechanisms that regulate prion protein expression is of great importance. It was previously shown that expression of the prion protein is to some degree regulated by an alternative promoter within intron 1. Studies using GFP and luciferase reporter systems were undertaken to determine key sites for the repression and ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…On the contrary, the down-regulation of PrP C expression has been observed in Cu-treated hypothalamic neurons (Toni et al 2005), meaning that the regulatory mechanisms depend on cell type. It is unlikely that cellspecific transcription factors are responsible for such variability, since those notoriously involved in P-rnp gene expression (Sp1, MTF-1, Ap-1, Ap-2, Atox-1) are ubiquitous (Bellingham et al 2009;Mahal et al 2001;Wright et al 2009). Based on previous epigenetic studies (Cabral et al 2002), a possible explanation could be that Cu deficiency acts in concert with unidentified cell-specific and ion-sensitive factors to disrupt the chromatin assembly and allow the accession of transcription factors to the P-rnp gene promoter.…”
Section: Discussionmentioning
confidence: 98%
“…On the contrary, the down-regulation of PrP C expression has been observed in Cu-treated hypothalamic neurons (Toni et al 2005), meaning that the regulatory mechanisms depend on cell type. It is unlikely that cellspecific transcription factors are responsible for such variability, since those notoriously involved in P-rnp gene expression (Sp1, MTF-1, Ap-1, Ap-2, Atox-1) are ubiquitous (Bellingham et al 2009;Mahal et al 2001;Wright et al 2009). Based on previous epigenetic studies (Cabral et al 2002), a possible explanation could be that Cu deficiency acts in concert with unidentified cell-specific and ion-sensitive factors to disrupt the chromatin assembly and allow the accession of transcription factors to the P-rnp gene promoter.…”
Section: Discussionmentioning
confidence: 98%
“…For example, YY1 and Hes-1 have been identified as repressors [9], [10], whereas E4BP4, Atox-1, SP1, MTF-1, and HSTF-1 have been identified as activators [9], [10], [11], [12]. Furthermore, some exogenous and endogenous stimulating factors, such as thermal stimuli, Cu 2+ , hyperbaric oxygen, NO, IGF-1, and nerve growth factor (NGF), are believed to play a role in PRNP regulation [12], [13], [14], [15], [16], [17], [18].…”
Section: Introductionmentioning
confidence: 99%
“…Although there are additional processes that can alter expression of prion protein (Wright et al 2009), in vitro studies have demonstrated prion protein expression to be modulated by the level of available copper in the medium (Toni et al 2005). In rats administered DEDC the levels of prion protein detected by western blot showed a biphasic response.…”
Section: Discussionmentioning
confidence: 99%